The assessment method of foreign language communication ability of intelligent emotional network based on artificial emotion - Li, Chen (Frontiers in Psychology, 2022)
The traditional evaluation methods of foreign language communication skills cannot deal with emotional information in the process of communication. Psychologists believe that a real personalized evaluation system should be smart. Based on the emotion network technology of artificial emotion intelligence, aiming at the shortcomings of the traditional evaluation system, this paper puts forward a new language ability evaluation system with certain emotion judgment function. The system can easily obtain and identify emotions in foreign communication, and can also carry out individual learning at the cognitive and emotional levels on the basis of comprehensive analysis of emotions and communication effects.